PERIODONTICS IN ARTIFICIAL INTELLIGENCE ERA : A LITERATURE REVIEW - Ni Wayan Arni Sardi; Ni Luh Putu Sri Maryuni Adnyasari; Made Talitha Suryaningsih Pinatih (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Artificial intelligence (AI) involves the creation of computer systems that imitate human actions, and it is progressively adopted as a supportive tool in aiding clinicians with disease diagnosis and treatment. One prevalent global ailment is periodontitis, which leads to the degradation and loss of the tooth-supporting tissues. The aim of this  review is to evaluate existing literature that delineates the influence of AI on diagnosing and studying the prevalence of this condition. Review: A Pubmed advanced search with narrative review was conducted of the past ten years using several search term such as “artificial Intelligences” and “periodontics”. Thorough searches were conducted on Pubmed in June 2023, encompassing studies where AI functioned as the independent variable for assessing, diagnosing, or treating patients with periodontitis. After eliminating duplicates, a total of 100 articles were recognized for preliminary abstract scrutiny. Of these, 76 documents were excluded, resulting in 24 texts for comprehensive evaluation. Conclusion: The development of artificial intelligence in the field of dentistry requires more systematic reviews and meta-analyses to enhance the knowledge and scope of artificial intelligence applications. AI models for periodontal applications are still under development and in the future, they have the potential to support diagnostic accuracy capability.